Pendidikan Guru Sekolah Dasar, Universitas San Pedro, Nusa Tenggara Timur, Indonesia - Tesalonika Veronika; Anita Mayosani Jacoba (Institute of Accounting Research and Novation (IARN), 2024)
This research investigates the impact of two distinct learning methods Team Quiz Method and Individual Quiz Method on students' mathematical problem-solving abilities. By comparing the performance of students engaged in group-based versus individual problem-solving tasks, the study aims to explore how collaborative and independent learning approaches affect cognitive processes involved in solving mathematical problems. Drawing on the theoretical frameworks of collaborative learning (Johnson & Johnson, 1989) and individual cognitive development (Vygotsky, 1978), the study assesses not only the outcomes but also the challenges and limitations inherent in each method. Findings indicate that students working collaboratively in teams demonstrated higher problem-solving performance, benefiting from peer interaction and collective problem-solving strategies. In contrast, individual learners showed slower progress, potentially due to a lack of feedback and peer-based support. The research highlights the importance of integrating both collaborative and individual methods in educational settings to maximize learning outcomes and suggests strategies for effectively assessing both group and individual contributions. The implications of these findings point to the need for educators to carefully balance and structure learning environments to support both independent and cooperative learning, ultimately enhancing students’ mathematical skills.